An antipsychotic drug exerts anti-prion effects by altering the localization of the cellular prion protein. - Claudia Stincardini; Tania Massignan; Silvia Biggi; Saioa R Elezgarai; Valeria Sangiovanni; Ilaria Vanni; Michael Pancher; Valentina Adami; Jorge Moreno; Matteo Stravalaci; Giulia Maietta; Marco Gobbi; et al. (PLoS ONE)
Prion diseases are neurodegenerative conditions characterized by the conformational conversion of the cellular prion protein (PrPC), an endogenous membrane glycoprotein of uncertain function, into PrPSc, a pathological isoform that replicates by imposing its abnormal folding onto PrPC molecules. A great deal of evidence supports the notion that PrPC plays at least two roles in prion diseases, by acting as a substrate for PrPSc replication, and as a mediator of its toxicity. This conclusion was recently supported by data suggesting that PrPC may transduce neurotoxic signals elicited by other disease-associated protein aggregates. Thus, PrPC may represent a convenient pharmacological target for prion diseases, and possibly other neurodegenerative conditions. Here, we sought to characterize the activity of chlorpromazine (CPZ), an antipsychotic previously shown to inhibit prion replication by directly binding to PrPC. By employing biochemical and biophysical techniques, we provide direct experimental evidence indicating that CPZ does not bind PrPC at biologically relevant concentrations. Instead, the compound exerts anti-prion effects by inducing the relocalization of PrPC from the plasma membrane. Consistent with these findings, CPZ also inhibits the cytotoxic effects delivered by a PrP mutant. Interestingly, we found that the different pharmacological effects of CPZ could be mimicked by two inhibitors of the GTPase activity of dynamins, a class of proteins involved in the scission of newly formed membrane vesicles, and recently reported as potential pharmacological targets of CPZ. Collectively, our results redefine the mechanism by which CPZ exerts anti-prion effects, and support a primary role for dynamins in the membrane recycling of PrPC, as well as in the propagation of infectious prions.